A phase 1b study of necitumumab in combination with abemaciclib in patients with stage IV non-small cell lung cancer. (November 2019) - Besse, Benjamin; Barlesi, Fabrice; Demedts, Ingel; Fuentes Pradera, Jose; Robinet, Gilles; Gazzah, Anas; Soldatenkova, Victoria; Frimodt-Moller, Bente; Kim, Jong Seok; Vansteenkiste, Johan
Highlights: Necitumumab is an anti-EGFR antibody; abemaciclib is a CDK4/6 inhibitor. Both have shown activity in patients with NSCLC and have non-overlapping toxicity. A single-arm, multicenter, phase 1b trial examined safety/efficacy of the combination. MTD of abemaciclib (150 mg Q12H) was identified for use with necitumumab. Combination safety profile similar to individual drugs, but efficacy not additive. Abstract: Objectives: Necitumumab, an anti-EGFR antibody, and abemaciclib, a CDK4/6 inhibitor, have shown activity in patients with non-small cell lung cancer (NSCLC) and have non-overlapping toxicities. A 2-part, single-arm, multicenter, phase 1b trial was conducted to test the safety and efficacy of necitumumab plus abemaciclib in patients with advanced NSCLC who had received ≤2 lines of chemotherapy, including a platinum-based one. Materials and Methods: Part A was a dose-escalation phase for abemaciclib (100, 150, 200 mg, Q12 H) in combination with necitumumab 800 mg D1D8 Q3W to determine the recommended dose for the expansion cohort, Part B. The primary endpoint was progression-free survival (PFS) rate at 3 months. Results: Sixty-six patients entered the study: 71% male, 41% squamous histology, 15% never-smokers. In Part A (n = 15), the maximum tolerated dose of abemaciclib was 150 mg Q12H in combination with necitumumab 800 mg. In 57 patients treated at this dose level, the 3-month PFS rate was 32.3% (95% CI: 20.4–44.8); median PFS was 2.14 months (1.41–2.76). The overall response rate (ORR) was 5.3% (1.1–14.6). The median OS was 6.93 months (4.96–12.85). In the exploratory subgroup analysis of EGFR expression-negative patients (n = 10), both the 3-month PFS and ORR were 0.0%. The most common grade 3 treatment-emergent adverse events were fatigue (14%), dyspnea (9%), diarrhea (7%), vomiting (7%), and hypokalemia (7%). Conclusions: Abemaciclib 150 mg Q12H with necitumumab 800 mg did not produce an additive effect over single-agent activity in patients with Stage IV NSCLC. The safety profile was consistent with the individual study drugs.